Pertimbangan Majelis Arbiter dalam Menetapkan CISG sebagai Applicable Substantive Law pada Arbitrase: Indonesia - Latifah, Emmy; Hartanto, Heri; Setiyawan, Anang; Maheswari, Yoan Amadina (Faculty of Law, Universitas Pasundan, 2024)
The United Nations Convention on Contracts for the International Sale of Goods (CISG) is an international legal instrument that can be chosen as the choice of law in international commercial contracts. Consequently, CISG is applied as the substantive law governing the resolution of disputes between contracting parties. However, in arbitration forums, the application of CISG as substantive law may vary depending on the considerations of the arbitral tribunal. This study aims to provide a comprehensive analysis of the considerations taken by arbitral tribunals when establishing CISG as the applicable substantive law in several international sale of goods cases. This research is normative legal research using statutory, case-based, and conceptual approaches, with data analyzed through legal interpretation methods. The findings of this study indicate that there are two conditions under which CISG is applied as the applicable substantive law, namely: (1) the application of CISG as the agreed choice of law by the parties; and (2) the application of CISG in situations where there is an absence of a choice of law.